2013
DOI: 10.1016/j.jcv.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The Multispot rapid HIV-1/HIV-2 differentiation assay is comparable with the Western blot and an immunofluorescence assay at confirming HIV infection in a prospective study in three regions of the United States

Abstract: In this study, Multispot confirmed HIV infections at a similar proportion to Western blot and IFA. Multispot, Western blot, and IFA, however, did not confirm all of the reactive Ag/Ab assay results and underscores the importance of HIV NAT testing to resolve discordant screening and confirmatory results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…who reported the difficulty to confirm the dual infection with HIV-1 and HIV-2 in a population of pregnant women in Abidjan [7]. Currently, HIV screening strategies in France [28] and in the United States [29, 30] are based on algorithms using a fourth generation assay which accurately detects early HIV infection but is unable to differentiate between HIV-1 and HIV-2. A Western Blot or a Multispot rapid HIV-1/HIV-2 differentiation assay is then used for the differentiation and in case of discordance a supplemental nucleic acid test (HIV-1 RNA) is performed [31].…”
Section: Discussionmentioning
confidence: 99%
“…who reported the difficulty to confirm the dual infection with HIV-1 and HIV-2 in a population of pregnant women in Abidjan [7]. Currently, HIV screening strategies in France [28] and in the United States [29, 30] are based on algorithms using a fourth generation assay which accurately detects early HIV infection but is unable to differentiate between HIV-1 and HIV-2. A Western Blot or a Multispot rapid HIV-1/HIV-2 differentiation assay is then used for the differentiation and in case of discordance a supplemental nucleic acid test (HIV-1 RNA) is performed [31].…”
Section: Discussionmentioning
confidence: 99%
“…This multispot assay detects and differentiates HIV-1 and HIV-2 antibodies in serum and plasma and was reported to confirm HIV infections at a proportion similar to that of the Western blot assay (9,10). The Bio-Rad Geenius HIV 1/2 confirmatory assay is a newer test which can also be used for the confirmation and differentiation of HIV-1 and HIV-2 infection.…”
mentioning
confidence: 99%
“…New developments also occur faster than evidence-based recommendations can be written. Ample evidence demonstrated that the FDA-approved Multispot HIV-1/HIV-2 differentiation assay provided results superior to those of the HIV-1 Western blot when used as a supplemental test [45,52,[79][80][81][82][83]. However, because it was approved only for HIV antibody screening, it could not be recommended as a supplemental test in diagnostic algorithms until the manufacturer obtained FDA approval for this intended use [84].…”
Section: The Three-legged Racementioning
confidence: 99%